Non-Revenue Water Analytics Model for the Intervention of Water Loss Program - Ahmad Masood, Ahmad Dzakwan (IRC, 2019)
Data analytics is a process of using raw data to make conclusions about a particular topic. With the help of current computing power and smart tools, the work of data analytics become more easier than before. Besides handling with big amount of data, the potential impact of using it is also big. In this project, data analytics has been used as a proof of concept to apply prevention approach to monitor Non-Revenue Water. Due to the large percentage of non revenue water in Malaysia which caused by unbilled water consumption, apparent losses and real losses, Malaysia was recorded losses estimated at 5,929 million litres per day (MLD) of treated water. The existing system are still lacking abilities to monitor and detect failure throughout water supply system effectively. The purpose of this project is to help utilities staff to make better decision making with the help of data analytics model. This project also suggest to build a predictive model to identify future failure in the system before it happens and losses occurs.